Sedimentary processes and facies of a desert fluvial system in southern Death Valley, California - Malicse, Jose Ariel Enriquez (Ann Arbor Michigan UMI Company, 1993)
Death Valley basin typifies a pull-apart strike-slip basin in an arid continental setting. The southern section of Death Valley basin is bordered by coalescing alluvial fans and is drained along its axis by the terminal end of the Amargosa River system. The terminal end of the Amargosa river was investigated with the following objectives: 1) to document the facies of an ephemeral stream in a hydrologically closed, pull-apart basin, and 2) to characterize its sand body geometries. The ephemeral fluvial system in southern Death Valley, California exhibits a succession of channel patterns and facies that can be divided into proximal, middle, and distal regions. The proximal region is narrow with steep gradient (3 to 5m/km), and is dissected by a single, straight braided channel with narrow, down-dip widening floodplain. The facies sequence in the proximal region is dominated by tabular lenses of crudely bedded gravel overlain by trough to planar cross-bedded coarse sand, and planar to ripple laminated fine sand. The proximal region grades down-dip into the low-gradient (0.5 to 1.7 m/km) anastomosing streams of the middle region. These anastomosing streams are characterized by interconnected networks of shallow, straight and meandering channels in a vast muddy floodplain. The straight channels have high width to depth ratio and are generally sandy; in contrast, the meandering channels have low width to depth ratio and are generally muddy. The migration of the anastomosing channels within the muddy floodplains produces isolated, thin (less than 1 m) sand bodies that are encased in a muddy facies. Their facies consist of massive to cross-bedded sand, ripple-laminated muddy sand, and wavy to planar laminated mud. The anastomosing system shows an overall decrease in its sand to mud ratio, and grades downdip into the nearly flat (less than 0.5 m/km) distal region. This distal region is characterized by few, shallow, straight to meandering muddy channels and widespread salt-encrusted to desiccated mudflats. The facies of the distal region consist of muddy facies with gypsum and halite crystals.--Abstract.
Thesis (Ph.D.)--Texas A & M University, 1993.
Keywords: Physical geography